Translanguaging in an EFL classroom discourse: To what extent it is helpful for the students? - Dinda Gusti Ayu Berlianti; Intan Pradita (Communications in Humanities and Social Sciences, 2021)
Translanguaging is a tool for bilingual or multilingual to learn more than one language. In the field of linguistic, translanguaging is not something new. However, its implementation is still found rare in higher education. To fill this void, this study aims to investigate the implementation of translanguaging in classroom, especially in higher education. This research was intended to answer how helpful translanguaging practices in EFL Classroom is. By using qualitative method, the data were collected by recording two credits full face-to-face classroom interaction. One lecturer and her forty-five students voluntarily became the research participants. The data were then analyzed by using thematic analysis. The findings showed that the practices were helpful in a way that the tutors could build an engaging dialogue for the students, enabling them to understand the complex learning materials. These findings then implied that in the teaching and learning process, EFL lecturers tend to be more attentive as they prefer to have their students understanding on complex subject to build English proficiency of their students’.